2007
DOI: 10.1007/s11121-007-0065-6
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine Use and Sexual Risk Behaviors in U.S. High School Students: Findings from a National Risk Behavior Survey

Abstract: Findings indicate that a substantial number of U.S. youth have used methamphetamine, that white and Hispanic high school students may be at higher risk for methamphetamine use, and that methamphetamine users may be at higher risk for engaging in sexual risk behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 34 publications
4
37
3
Order By: Relevance
“…Hence, Meth-pretreated males did not have impaired associative memory or reduced sensitivity to LiCl or LiCl-induced illness. It appears that Meth pretreatment caused maladaptive or compulsive sex seeking, despite learned negative consequences, which is in line with human reports (Frosch et al, 1996;Halkitis et al, 2001;McKirnan et al, 2001;Rawson et al, 2002;Somlai et al, 2003;Green and Halkitis, 2006;Springer et al, 2007).…”
Section: Discussionsupporting
confidence: 83%
“…Hence, Meth-pretreated males did not have impaired associative memory or reduced sensitivity to LiCl or LiCl-induced illness. It appears that Meth pretreatment caused maladaptive or compulsive sex seeking, despite learned negative consequences, which is in line with human reports (Frosch et al, 1996;Halkitis et al, 2001;McKirnan et al, 2001;Rawson et al, 2002;Somlai et al, 2003;Green and Halkitis, 2006;Springer et al, 2007).…”
Section: Discussionsupporting
confidence: 83%
“…Lifetime meth use in this sample of pregnant AI teens was up to 3 times higher than among previous national samples of AI/AN adolescents (Oetting et al, 2000) and approximately 5 times higher than U.S. All Races adolescents (Springer, Peters, Shegog, White, & Kelder, 2007;Johnston et al, 2006). Past-month use of meth (2.5%) was double past-month use in comparable samples of U.S. All Races youth (Iritani, Hallfors, & Bauer, 2007 fi nding is consistent with another large prospective study of western AI adolescents, which showed that initiation of marijuana use prior to alcohol use increased the risk of substance use progression (Novins & Barón, 2004).…”
Section: Drug Usecontrasting
confidence: 63%
“…21,22 Other methamphetamine-associated sexual risks include being pregnant or getting someone pregnant 23 and early age of sexual debut. 24 Girls also appear to have more psychiatric problems related to methamphetamine use than boys, 25 and greater treatment-seeking for methamphetamine. 26 The limited research on methamphetamine use among incarcerated adolescents has shown high rates of use among this population.…”
Section: Health Concerns Among Incarcerated Female Adolescentsmentioning
confidence: 97%